Mitogen-Activated Protein Kinases in Endothelial Pathophysiology. (1st November 2003) - Bogatcheva, Natalia V.; Dudek, Steven M.; Garcia, Joe G. N.; Verin, Alexander D.
Abstract : Endothelial cells continuously respond to extracellular stimuli such as chemical signals produced by circulating blood elements or mechanical forces such as shear stress. Proinflammatory cytokines, mitogens, reactive oxygen species, and shear stress trigger signal molecules to initiate multiple intracellular pathways, which often converge at mitogen-activated protein (MAP) kinase activation. The MAP kinase superfamily represents a burgeoning area of clinical investigation for treatment of various inflammatory and oncologic diseases and plays an essential role in mediating response to infection, ischemia/reperfusion injury, and vessel healing and remodeling through regulation of such diverse phenomena as endothelial cell proliferation, migration, apoptosis, and endothelial barrier function. The downstream effects of MAP kinase activation include modulation of gene expression via up-regulation of various transcription factors. In addition to these sustained effects, MAP kinases coordinate more immediate responses that affect dynamic cytoskeletal rearrangements necessary for cell migration and regulation of barrier function. This review discusses the important regulatory roles of MAP kinases in the vital physiologic functions of endothelium, focusing mainly on the role of MAP kinases in the maintenance of endothelial barrier.